Inventory, sustainability assessment, and upscaling of best agricultural water management practices - Loulseged, Makonnen; Awulachew, Seleshi Bekele; Jayasinghe, Gayathree; Hagos, Fitsum; Erkossa, Teklu (2011)
It is the belief of many analysts that agrarian countries like Ethiopia that depend on rain-fed agriculture are significantly vulnerable to rainfall variability, the risk which tends to aggravate with global climate change. Consequently, it is believed that future increases in food supplies and economic prosperity depend heavily on effective agricultural water management. It is with this in mind that the use of low-cost technologies for rainwater and runoff control, storage, water lifting, conveyance and application have become more widespread in Ethiopia since the recent drought of 2002/2003. A range of technologies are currently used with varying levels of impacts. This paper outlines an inventory, characterization, suitability and upscaling aspects of Agricultural Water Management Technologies (AWMT) in Ethiopia. Particular characteristics of each of the technologies, their suitability for a given environment, and the necessary conditions for their successful adoption and scaling up are identified. Furthermore, a variety of combinations of technologies used for control or storage, lifting, conveyance and application of rainwater are documented. Suitability of a technology in a particular environment depends on many factors, such as, the nature of technical complexity, the existing institutional and individual capacity to implement, the costs and benefits, etc. Technical considerations include implementation (set up), operation and maintenance, affordability and environmental impact. The results of a ranking exercise of the technical complexity of a given technology are presented. Concerns related to waterborne and water-related diseases due to stagnation, water quality and possibility of mosquito breeding are discussed. Households in some parts of Ethiopia, who have practiced improved agricultural water management suitable to their local conditions, have managed to diversify their incomes through beekeeping, livestock, intercropping cash crops with food crops and setting up shops, hotels and flour mills in the nearby towns or villages. Therefore, AWMT at smallholder level meet the intended purpose, provided that they are suitable and adaptable to the local circumstances. The question is which of the technologies are suitable to which area under what socioeconomic conditions?